Congenital Insensitivity to Pain with Recurrent Septic Arthritis of the Left Knee - Z, Zamzuri; KL, Goh; CA, Aminuddin; MA, Mohamed Azril; A, Shukrimi (IIUM Medical Journal Malaysia, 2011)
A 15-year –old Malay male with congenital insensitivity to pain presented with recurrent septic arthritis of the left knee complicated by osteomylitis. Repeated arthrotomy and wound debridement was done, however, the condition was not resolved. Amputation was suggested as the best method of treatment to eradicate the infection.